Ice mass balance of the Bellingshausen ice cap in 2007–2012 (King George Island, South Shetland Islands, Antarctica) - B. R. Mavlyudov (Лëд и снег)
Mass balance researches on Bellingshausen Ice Dome (King George Island, archipelago Southern Shetland Islands, Antarctica) were spent during five summer seasons in 2007–1012 and one winter in 2011. The analysis of received data has shown that in 2007/08 and 2008/09 ice mass balance on Bellingshausen Ice Dome was almost closed to zero, in 2009/10, 2010/11 and 2011/12 it was positive. ELA in 2007/08 and 2008/09 was situated a little below top of the Ice Dome (about 225 m a.s.l.), in 2009/10 ELA has lowered practically up to sea level, in 2010/11 it was equal 180 m a.s.l., in 2011/12 – 220 m a.s.l. Good correlation between snow and ice melting and mean summer air temperature give possibility to renew ice melting conditions for all period of observations at Bellingshausen weather station (1969–2011). Ice mass balance for Bellingshausen Ice Dome was also renewed for similar period. Analysis of received data allow to suppose that tendency of climate cooling is outlined in last years.